A simple and efficient PCR method for the detection of Agrobacterium tumefaciens in plant tumours - Cubero, Jaime; Martínez, M. Carmen; Llop, Pablo; López, María M. (Society for Applied Microbiology, 2022)
A simple PCR protocol was developed for identifying Agrobacterium as the causal agent of the tumours produced by this bacterium in plant material. The sensitivity of this method was compared with that of bacterial isolation using common and selective media with a previous enrichment step. More than 200 samples from tumours of naturally infected and inoculated plants from several hosts including almond, peach×almond hybrids, apricot, rose, tobacco, tomato, raspberry, grapevine and chrysanthemum, were analysed by both methods. PCR was the most efficient method for detecting the bacterial aetiology of the plant tumours. Agrobacterium tumefaciens was better detected in crown and root tumours than in aerial tumours with all the methods assayed in inoculated plants. A comparison between the efficiency of the diagnosis by analysing pieces from the external and internal part of the tumour showed no differences between them.